A Rasch analysis of the model of human occupation screening tool single observation form (MOHOST-SOF) in mental health. (January 2016) - Maciver, Donald; Morley, Mary; Forsyth, Kirsty; Bertram, Nick; Edwards, Tracey; Heasman, David; Rennison, Jane; Rush, Robert; Willis, Suzie
Introduction: This study examined the psychometric properties of the model of human occupation screening tool single observation form. Method: Clinical records were extracted pre- and post-treatment for 152 mental health service users. Data were model of human occupation screening tool single observation form scores and demographics. We investigated the form using Rasch analysis; we also present an analysis of change over time. Results: We identified four misfitting items and evidence of instability with respect to change over time. After anchoring to adjust for unstable estimates, it was possible to measure client change, and there were significant differences in form scores pre–post treatment indicating client improvement in ability. Conclusion: The study provides initial psychometric assessment of this version of the model of human occupation screening tool.